Chronic obstructive pulmonary disease as a risk factor for cognitive impairment: a systematic review and meta-analysis - Yang Zhao; Shu Li; Xia Chen; Zhenjie Yu (BMJ Open Respiratory Research)
Background Cognitive impairment is affecting plenty of patients with chronic obstructive pulmonary disease (COPD), and it is the main leading cause of quality of life to varying degrees. However, there are still wide discrepancies in these prevalence rates can be attributed to the diversity in study designs, participant age ranges, inclusion criteria and the methodologies used for assessment. Previous studies revealed the association between COPD and cognitive impairment, but the conclusions remain controversial.Objectives The current systematic review aimed to investigate whether COPD is an independent risk factor for cognitive impairment.Study design A systematic review and meta-analysis.Data sources PubMed, Cochrane Library, MEDLINE, Embase, Web of Science, China Knowledge Resource Integrated Database, Wanfang Database, Chinese Biomedical Database and Weipu Database were searched from inception to 1 December 2022.Eligibility criteria The inclusion criteria involved studies that reported cognitive impairment in COPD. We just included cohort designs, published in English or Chinese language.Data extraction and synthesis Two reviewers independently extracted and assessed the quality of data using Newcastle-Ottawa Quality Assessment Scale. The outcomes were assessed with random-effects model and reported as the HR with 95% CI using the Review Manager software.Results 12 studies from 10 articles reporting on 625 644 people were included. The findings indicated that compared with those without COPD at baseline, patients with COPD were associated with an increased risk of cognitive impairment. Subgroup analysis showed the association was not significantly different in sex and age, and the subgroup supports that COPD has a higher risk of non-amnestic mild cognitive impairment (na-MCI) than amnestic MCI.Conclusions Patients with COPD have a higher risk of developing cognitive impairment and are more likely to cause na-MCI compared with those without COPD, and this risk is not affected by gender or age. Therefore, continuous monitoring of cognitive function in COPD is critical.PROSPERO registration number CRD42021285913.